2009
DOI: 10.3329/jsr.v1i3.2114
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of Periphyton-based Aquaculture Technology in Rice-fish Environment

Abstract: Periphyton is being used traditionally as rich aquatic feed for fishes throughout the countries like Cambodia, West Africa, Srilanka, India and Bangladesh. In waterlogged rice environment, it can be judiciously utilized as feed source introducing periphytophagous fish. Studies supported rice straw as suitable substrate for periphyton growth. The study of gut content of Common carp (Cyprinus carpio L.) from a periphyton-based rice-fish culture system in Apatani Plateau of Arunachal Pradesh, India showed maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This study demonstrates the benefits of bamboo substrates in cages for Nile tilapia farming, at least until they reach 500 g. While in ponds, studies have attested the potential of periphyton as a robust source of quality food for stocked fish (Keshavanath et al, 2004;Saikia and Das, 2009), in cages neither Norberg (1999) nor Huchette and Beveridge (2003) found periphyton-based cage culture to be viable. In floating cages in an earthen pond, Sakr et al (2015) showed that the reduction in dietary protein levels in the presence of periphyton substrates improved the performance of Nile tilapia juveniles and increased the costeffectiveness in relation to the traditional strategy of providing tilapia with higher levels of protein and no periphyton.…”
Section: Discussionmentioning
confidence: 93%
“…This study demonstrates the benefits of bamboo substrates in cages for Nile tilapia farming, at least until they reach 500 g. While in ponds, studies have attested the potential of periphyton as a robust source of quality food for stocked fish (Keshavanath et al, 2004;Saikia and Das, 2009), in cages neither Norberg (1999) nor Huchette and Beveridge (2003) found periphyton-based cage culture to be viable. In floating cages in an earthen pond, Sakr et al (2015) showed that the reduction in dietary protein levels in the presence of periphyton substrates improved the performance of Nile tilapia juveniles and increased the costeffectiveness in relation to the traditional strategy of providing tilapia with higher levels of protein and no periphyton.…”
Section: Discussionmentioning
confidence: 93%
“…The phosphorus capturing capacity enables periphyton as a potential bio-fertilizer (Crispim et al 2009;Saikia and Das 2009), but the safety should be considered due to the complex composition of the waters such as heavy metal and toxic elements. Fortunately, periphyton from paddy fields is relatively safe to use as a bio-fertilizer because the soil and water in paddy field are usually nontoxic.…”
Section: Discussionmentioning
confidence: 99%
“…In their work, Saikia and Das (, ) observed much higher values of dry matter (DM) and ash‐free dry matter (AFDM) on rice stem than artificial substrate. The overall DM and AFDM increase as the rice field progresses towards flood phase.…”
Section: Agro‐ecology Of Ricefish Farmingmentioning
confidence: 97%
“…Most of the attached forms including Bacillariophyceae are secured to living on substrate by jelly‐like secretions, while others are attached to gelatinous stalks (Patrick ). However, the submerged part of the rice stem favours maximum adherence of algal communities and increases additional surface area for resource exploration (Saikia & Das ). For instance, in Apatani Plateau, the rice stems provide an extra surface area of more than 1000 m 2 for the endemic cultivar known as ‘amo’ with stem diameter of 1.0–1.3 cm submerged into 20–30 cm water in the field (Saikia ).…”
Section: Agro‐ecology Of Ricefish Farmingmentioning
confidence: 99%